Barriers and facilitators to implementation of shared medical appointments in primary care for the management of long-term conditions: a systematic review and synthesis of qualitative studies - Falko F Sniehotta; Eileen Kaner; Amy O'Donnell; Fiona Graham; Helen Martin; Katherine Jackson; Mei Yee Tang; Oladapo Ogunbayo (BMJ Open)
Objective To synthesise the published literature on practitioner, patient and carer views and experiences of shared medical appointments (SMAs) for the management of long-term conditions in primary care.Design Systematic review of qualitative primary studies.Methods A systematic search was conducted using MEDLINE (Ovid), PsycINFO (Ovid), CINAHL (EBSCOhost), Web of Science, Social Science Premium Collection (Proquest) and Scopus (SciVerse) from database starting dates to June 2019. Practitioner, patient and carer perspectives were coded separately. Deductive coding using a framework approach was followed by thematic analysis and narrative synthesis. Quality assessment was conducted using the Critical Appraisal Skills Programme for qualitative studies.Results We identified 18 unique studies that reported practitioner (n=11), patient (n=14) and/or carer perspectivs(n=3). Practitioners reported benefits of SMAs including scope for comprehensive patient-led care, peer support, less repetition and improved efficiency compared with 1:1 care. Barriers included administrative challenges and resistance from patients and colleagues, largely due to uncertainties and unclear expectations. Skilled facilitators, tailoring of SMAs to patient groups, leadership support and teamwork were reported to be important for successful delivery. Patients’ reported experiences were largely positive with the SMAs considered a supportive environment in which to share and learn about self-care, though the need for good facilitation was recognised. Reports of carer experience were limited but included improved communication between carer and patient.Conclusion There is insufficient evidence to indicate whether views and experiences vary between staff, medical condition and/or patient characteristics. Participant experiences may be subject to reporting bias. Policies and guidance regarding best practice need to be developed with consideration given to resource requirements. Further research is needed to capture views about wider and co-occurring conditions, to hear from those without SMA experience and to understand which groups of patients and practitioners should be brought together in an SMA for best effect.PROSPERO registration number CRD42019141893.